Acute cardiorespiratory, perceptual and enjoyment responses to high-intensity interval exercise in adolescents. Issue 10 (26th November 2017) - Malik, Adam A.; Williams, Craig A.; Bond, Bert; Weston, Kathryn L.; Barker, Alan R.
Abstract: This study aimed to examine adolescents' acute cardiorespiratory and perceptual responses during high-intensity interval exercise (HIIE) and enjoyment responses following HIIE and work-matched continuous moderate intensity exercise (CMIE). Fifty-four 12- to 15-year olds (27 boys) completed 8 × 1-min cycling at 90% peak power with 75-s recovery (HIIE) and at 90% of the gas exchange threshold (CMIE). Absolute oxygen uptake ( ), percentage of maximal (% ), heart rate (HR), percentage of maximal HR ( % HRmax ) and ratings of perceived exertion (RPE) were collected during HIIE. Enjoyment was measured using the physical activity enjoyment scale (PACES) following HIIE and CMIE. Boys elicited higher absolute during HIIE work ( p < .01, effect size (ES) > 1.22) and recovery ( p < .02, ES > 0.51) intervals but lower % during HIIE recovery intervals compared to girls ( p < .01, ES > 0.67). No sex differences in HR and %HRmax were evident during HIIE and 48 participants attained ≥90% HRmax . Boys produced higher RPE at intervals 6 ( p = .004, ES = 1.00) and 8 ( p = .003, ES = 1.00) during HIIE. PACES was higher after HIIE compared with CMIE ( p = .003, ES = 0.58). Items from PACES "I got something out of it", "It's very exciting" and "It gives me a strong feeling of success" were higher after HIIE (all p < .01, ES > 0.32). The items "I feel bored" and "It's not at all interesting" were higher after CMIE (all p < .01, ES > 0.46). HIIE elicits a maximal cardiorespiratory response in most adolescents. Greater enjoyment after HIIE was due to elevated feelings of reward, excitement and success and may serve as a strategy to promote health in youth.